Functional and Evolutionary Analysis of the CASPARIAN STRIP MEMBRANE DOMAIN PROTEIN Family. Issue 4 (11th June 2014) - Roppolo, Daniele; Boeckmann, Brigitte; Pfister, Alexandre; Boutet, Emmanuel; Rubio, Maria C.; Dénervaud-Tendon, Valérie; Vermeer, Joop E.M.; Gheyselinck, Jacqueline; Xenarios, Ioannis; Geldner, Niko
Abstract : Casparian strip membrane proteins are potentially involved in the generation of plasma membrane domains and the modification of cell walls. Abstract: CASPARIAN STRIP MEMBRANE DOMAIN PROTEINS (CASPs) are four-membrane-span proteins that mediate the deposition of Casparian strips in the endodermis by recruiting the lignin polymerization machinery. CASPs show high stability in their membrane domain, which presents all the hallmarks of a membrane scaffold. Here, we characterized the large family of CASP-like (CASPL) proteins. CASPLs were found in all major divisions of land plants as well as in green algae; homologs outside of the plant kingdom were identified as members of the MARVEL protein family. When ectopically expressed in the endodermis, most CASPLs were able to integrate the CASP membrane domain, which suggests that CASPLs share with CASPs the propensity to form transmembrane scaffolds. Extracellular loops are not necessary for generating the scaffold, since CASP1 was still able to localize correctly when either one of the extracellular loops was deleted. The CASP first extracellular loop was found conserved in euphyllophytes but absent in plants lacking Casparian strips, an observation that may contribute to the study of Casparian strip and root evolution. In Arabidopsis ( Arabidopsis thaliana ), CASPL showed specific expression in a variety of cell types, such as trichomes, abscission zone cells, peripheral root cap cells, and xylem pole pericycle cells.